2011
DOI: 10.4103/0378-6323.77455
|View full text |Cite
|
Sign up to set email alerts
|

Topical corticosteroid abuse on the face: A prospective, multicenter study of dermatology outpatients

Abstract: This was an OPD-based study and, therefore, it may or may not accurately reflect the community data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
188
8
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(227 citation statements)
references
References 11 publications
22
188
8
9
Order By: Relevance
“…10 Saraswati A et al and Inakanti Yet al observed high incidence of acneiform eruption in their study of 57.5 % and 88.5% respectively. 3,8 It was observed that on short term use, the TCs had good results in controlling acne while the situation worsened on continuous long time application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Saraswati A et al and Inakanti Yet al observed high incidence of acneiform eruption in their study of 57.5 % and 88.5% respectively. 3,8 It was observed that on short term use, the TCs had good results in controlling acne while the situation worsened on continuous long time application.…”
Section: Discussionmentioning
confidence: 99%
“…3,8 The 58:42 ratio of rural to urban population is a clear indication of ubiquitous presence of this problem. In rural areas, another major problem was the web of village doctors who were prescribing authority in 14% of cases in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Топические стероиды применяются для актив-ного терапевтического воздействия на очаг пораже-ния с целью ликвидации воспалительных проявле-ний, восстановления целостности и нормальной структуры кожного покрова, снижения интенсив-ности зуда [11,12].…”
unclassified
“…Many patients prefer to use topical steroids as a fairness cream (9). To minimize adverse cutaneous and systemic reactions, especially with prolonged use, the rational use of topical steroids should include careful consideration of the patient's age, total area of application, quantity to be applied, efficacy of the selected corticosteroid, and frequency of application (10).…”
mentioning
confidence: 99%